Riscos da desinformação: uma análise sobre a atuação da Agência Lupa no contexto da Covid-19 de 2020 a 2022 - Almeida, Daiana Calixto de (2023)
Society presents at the heart of everyday life the emergence of social phenomena arising from human actions, these in turn are directly related to the reality of each era, they are reflections of the way in which individuals organize themselves socially and what they produce from this. Technologies are constantly being modified and improved and communication and social interaction accompanies these transformations. All of this ends up allowing people to start taking advantage of the tools that exist to interact with each other and the impacts of their actions start to clearly manifest themselves in society in all social spheres. Since the emergence of virtual social networks and their increasing use, increasingly complex phenomena have emerged due to strong human interaction and the large flow of information exchange resulting from this process. Social networks became spaces for representing everyday life and reality began to be represented on screens, thus gaining greater dimension and impact. The phenomenon of misinformation is the result of these factors, where the exchange of content that occurs in these spaces ends up contributing to false, misleading and distorted news gaining more reach and power. The Covid-19 pandemic has made it even more evident how information conveyed on social networks can gain potential due to the culture of sharing. The dissemination of misinformation related to the pandemic on social networks was capable of changing behaviors and strongly interfering in the configuration, organization and functioning of society. This is a fact that has been and is being observed daily. We have already seen chaotic and difficult-to-control situations being caused due to this problem. This work focuses on the analysis and investigation of disinformation and consequently the phenomenon of Infodemic related to the Covid-19 pandemic context. We seek to provide insights and analyze how this occurs, what evidence it has and what are the main measures that can be taken to combat it.